Carotid body potentiation during chronic intermittent hypoxia: implication for hypertension - Del Rio, Rodrigo (Front Physiol, 2014)
Autonomic dysfunction is involved in the development of hypertension in humans with obstructive sleep apnea, and animals exposed to chronic intermittent hypoxia (CIH). It has been proposed that a crucial step in the development of the hypertension is the potentiation of the carotid body (CB) chemosensory responses to hypoxia, but the temporal progression of the CB chemosensory, autonomic and hypertensive changes induced by CIH are not known. We tested the hypothesis that CB potentiation precedes the autonomic imbalance and the hypertension in rats exposed to CIH. Thus, we studied the changes in CB chemosensory and ventilatory responsiveness to hypoxia, the spontaneous baroreflex sensitivity (BRS), heart rate variability (HRV) and arterial blood pressure in pentobarbital anesthetized rats exposed to CIH for 7, 14, and 21 days. After 7 days of CIH, CB chemosensory and ventilatory responses to hypoxia were enhanced, while BRS was significantly reduced by 2-fold in CIH-rats compared to sham-rats. These alterations persisted until 21 days of CIH. After 14 days, CIH shifted the HRV power spectra suggesting a predominance of sympathetic over parasympathetic tone. In contrast, hypertension was found after 21 days of CIH. Concomitant changes between the gain of spectral HRV, BRS, and ventilatory hypoxic chemoreflex showed that the CIH-induced BRS attenuation preceded the HRV changes. CIH induced a simultaneous decrease of the BRS gain along with an increase of the hypoxic ventilatory gain. Present results show that CIH-induced persistent hypertension was preceded by early changes in CB chemosensory control of cardiorespiratory and autonomic function.